ANALISIS PENGGUNAN MEDIA E-COMMERCE DALAM MENDUKUNG PERKEMBANGAN USAHA MENURUT PERSPEKTIF MANAJEMEN BISNIS SYARIAH (Studi kasus pada Toko Angel Bukittinggi) - Sri Rahayu; Sandra Dewi (CV. Adiba Aisha Amira, 2025)
Angel Bukittinggi Shop which is one of the women's clothing stores. Where now shopping is known in various circles, and in the Bukittingi market at this time a little, there are still some of them who have not utilized e-commerce media in marketing based on a lack of understanding in online sales and are more focused on resellers and direct purchases. And there is a decline in the level of sales in the marketplace media where the marketplace is less in demand by the community today. The research method used is qualitative, namely research whose data is in the form of words (not numbers) which come from interviews, report notes, documents and others. The results of the study showed that there was a decline in sales at Angel Shop due to the lack of public interest in the marketplace media, of course business owners can hold discount offers, and hold big giveaways, this can be a concern and also customer buying interest in Angel Shop. Angel Shop has utilized e-commerce media but some business actors have not utilized the media because the actors are more focused on sales in large scale. Angel Shop has implemented various steps that reflect the principles of sharia business, such as honesty, transparency, and fairness in every transaction. The use of e-commerce media can support business development in the future because customers are more interested in using e-commerce media, because by purchasing on e-commerce media, customers feel it is easier without having to come to the store.